2020
DOI: 10.7554/elife.54160
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic and antagonistic drug interactions in the treatment of systemic fungal infections

Abstract: Invasive fungal infections cause 1.6 million deaths annually, primarily in immunocompromised individuals. Mortality rates are as high as 90% due to limited treatments. The azole class antifungal, fluconazole, is widely available and has multi-species activity but only inhibits growth instead of killing fungal cells, necessitating long treatments. To improve treatment, we used our novel high-throughput method, the overlap2 method (O2M) to identify drugs that interact with fluconazole, either increasing or decre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 98 publications
1
39
0
1
Order By: Relevance
“…On another note, high‐throughput screenings (HTSs) of chemical libraries have been shown to represent efficient approaches for the identification of synergistic combinations of antimicrobials (i.e. the combined efficacy of two antimicrobials is greater than the sum of their individual effects; Wambaugh et al ., 2020). Remarkably, given the low rates in the discovery of new antimicrobials nowadays, the synergistic combination therapy not only offers the possibility to revitalize the use of existing antibiotics, but also increases the activity spectrum of the treatment, minimizes host toxicity and reduces the occurrence of AMR as synergistic drugs generally act against different cellular targets (Tyers and Wright, 2019).…”
mentioning
confidence: 99%
“…On another note, high‐throughput screenings (HTSs) of chemical libraries have been shown to represent efficient approaches for the identification of synergistic combinations of antimicrobials (i.e. the combined efficacy of two antimicrobials is greater than the sum of their individual effects; Wambaugh et al ., 2020). Remarkably, given the low rates in the discovery of new antimicrobials nowadays, the synergistic combination therapy not only offers the possibility to revitalize the use of existing antibiotics, but also increases the activity spectrum of the treatment, minimizes host toxicity and reduces the occurrence of AMR as synergistic drugs generally act against different cellular targets (Tyers and Wright, 2019).…”
mentioning
confidence: 99%
“…Chemical–genetic mapping of synergistic compound pairs has been explored in Saccharomyces cerevisiae , but pathogen-specific analyses have revealed that many compounds display species-specific chemical–genetic interactions 118 . A high-throughput approach has been developed to predict synergistic and antagonistic drug pairs using at least one known synergistic drug pair and chemical–genetic data sets 118 , 119 . This approach, termed the overlap 2 method, has been applied to both fungal and bacterial pathogens.…”
Section: Drug Combination Therapymentioning
confidence: 99%
“…This approach, termed the overlap 2 method, has been applied to both fungal and bacterial pathogens. For example, the overlap 2 method was applied to a compound library enriched for FDA-approved compounds against C. neoformans 116 119 and successfully predicted that the anticholinergic drug dicyclomine HCl with fluconazole would serve as a potent anti-cryptococcal combination therapy. Indeed, the combination of these drugs displayed enhanced efficacy in a mouse model of cryptococcal meningitis 119 .…”
Section: Drug Combination Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, if further research were to confirm that pathogen growth is enhanced in combined infection, combinatorial treatment with drugs that have a synergistic or dual effect would be indicated. In this respect, some new azoles have been described to have anti- P. aeruginosa activity [ 151 ] and some antibacterial drugs have direct antifungal activity [ 152 , 153 ] and/or synergise with common antifungals [ 154 , 155 , 156 , 157 ]. In contrast, if the major effect of the interaction were to trigger secretion of a toxic compound, a virulence blocker would be beneficial.…”
Section: Future Directions For Clarifying a Fumigatus-pmentioning
confidence: 99%